The The Effect of Transformational Leadership and Knowledge Management on Lecturer Performance in State Polytechnic of Sriwijaya - Irma Salamah; RD Kusumanto (Kusuma Negara Business School, 2021)
This study aims to analyze and find out how the influence of transformational leadership and knowledge management on the performance of Sriwijaya State Polytechnic lecturers. This research is a quantitative research, data obtained from questionnaires distributed to lecturers of the Sriwijaya State Polytechnic with a total sample of 65 people. The sampling technique is convenience sampling. The data was processed using SPSS 22. The analysis technique used Multiple Linear Regression. The test results obtained partially transformational leadership does not affect the performance of the Sriwijaya State Polytechnic lecturers and partially knowledge management affects the performance of Sriwijaya State Polytechnic lecturers.